Hubungan Technology Acceptance Models (TAM), Gaya Hidup, Produk dan Kepercayaan Konsumen terhadap Keputusan Pembelian Toko Daring - Abdul Malik Sayuti; Wahyu Rafdinal; Chandra Budhi Septyandi (Applied Business and Administration Journal, 2022)
This study aims to analyze the importance of online store features in influencing customer’s purchasing decisions on online stores. This study uses the theory of acceptance model in analyzing the factors of technology acceptance in online stores and effect of lifestyle, product, trust on online purchase decision. Respondents in this study are 180 peoples who have bought fashion products in the online stores. The selection of samples using convenience sampling technique is a sampling procedure that selects samples from people or units that are most easily found or accessed. The data analysis technique used is Structural Equation Model based on Partial Least Square (SEM-PLS). The results show that perceived usefulness of the technology acceptance model in the online store affect purchasing decisions at the online store. Lifestyle, products, usefullnes of technology in online stores, and trust play an important role in influence on Purchase Decisions on the online store. The results have no moderating effect on online purchase decision.